Cerium oxide nanoparticle-loaded polyvinyl alcohol nanogels delivery for wound healing care systems on surgery - Lianlian Cao; Guojing Shao; Fengmei Ren; Minghua Yang; Yan Nie; Qian Peng; Peng Zhang (Taylor & Francis Group, 2021)
This study was designed to establish the composition of wound bandages based on Cerium nanoparticle (CeNP)-loaded polyvinyl alcohol (PVA) nanogels. The CeNP nanogel (Ce-nGel) was fabricated by the fructose-mediated reduction of Cerium oxide solutions within the PVA matrix. The influences of different experimental limitations on PVA nanogel formations were examined. The nanogel particle sizes were evaluated by transmission electron microscopy and determined to range from ∼10 to 50 nm. Additionally, glycerol was added to the Ce-nGels, and the resulting compositions (Ce-nGel-Glu) were coated on cotton fabrics to generate the wound bandaging composite. The cumulative drug release profile of the Cerium from the bandage was found to be ∼38% of the total loading after two days. Additionally, antibacterial efficacy was developed for Gam positive and negative microorganisms. Moreover, we examined in vivo healing of skin wounds formed in mouse models over 24 days. In contrast to the untreated wounds, rapid healing was perceived in the Ce-nGel-Glu-treated wound with less damage. These findings indicate that Ce-nGel-Glu-based bandaging materials could be a potential candidate for wound healing applications in the future.